The problem of identification of foreign public officials in combating the legalization (laundering) of the proceeds of crime and the financing of terrorism - Elmanova A. K., Gobrusenko K. I. (Interactive science, 2017)
this article discusses the issues of optimization organization of identification of foreign public officials with the aim of countering legalization (laundering) of criminal proceeds as well as the ways to improve identification of foreign public officials on the territory of the Russian Federation taking into account the Russian legislation.
Keywords: база данных; законодательные акты; противодействие легализации (отмыванию) доходов; иностранное публичное должностное лицо; финансовое расследование; countering legalization (laundering) criminal proceeds; foreign public officials; financial investigation; legislative acts; data base